CRITICAL INCIDENTS IN PHYSICAL EDUCATION - Rui Resende; Nuno Pimenta; Paulo Sá (Journal of Physical Education)
ABSTRACT Evaluate the student’s satisfaction in Physical Education (PE) classes can contribute to help teachers in developing strategies to better planning and get students more motivated. The aim of this study is to describe what students’ value most and why in a PE class. It was used a qualitative and descriptive approach of the critical incidents in a PE classroom interviewing 278 Portuguese students. The results reveal in the satisfaction striking moments, playing and compete, getting individually and collective success in a satisfactory class climate. The less welcome striking moments were a mixture of playing, compete and failure. The warmup and negative class climate also were reported as not very gratifying. The fun moments reported were personal realization, pleasure and sharing. The teacher appreciation reveals pedagogical interactions, specific knowledge and personal conduct. The students like PE classes. Planning by the PE teacher should maximize opportunities of enjoyable situations by the students, in order to improve their motivation.